Antioxidant effect of Arrabideae chica (crajiru) extract on oxidative stress in diabetic rats - Perlles Gomes Bandeira e Sousa, Paula; Medeiros Azevedo, Ítalo; Cunha Medeiros , Aldo (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2021)
Objective: This study aimed to investigate the effects of the antioxidant potential of Arrabideae chica (crajiru) extract on oxidative stress in diabetic rats. Methods: Adult Wistar rats (Rattus norvegicus), weighing 238±12g were divided into three groups of six rats each: CN normal untreated control; DIAB+NS diabetic rats treated with normal saline; and diabetic rats treated with crajiru extract, DIAB+CR. The CN and DIAB+NS groups (control groups) received normal saline solution (NS) orally (gavage); rats in the DIAB+CR group received crajiru extract (300 mg/kg) once a day by gavage for 6 weeks. Measurements of urea and creatinine in serum, and kidney tissue catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) were performed. The variables were assessed using the Tukey test, significance p<0.05. Results: All animals survived the experiments. In the CN group, compared with the DIAB+NS group, there was significant difference between the levels of glycemia on the second day of dosing and on the 10th day (p<0.05). No difference was observed on glycemia comparing the 2th and 10th day on the rats of group C+NS (p>0.05). Diabetic animals from DIAB+CR group had a significant reduction in glycemia on 10th day of treatment, comparing the 2nd day (p<0.05). There was a significant reduction in glycemia in the DIAB+CR group, comparing with the DIAB+NS group (p<0.05). There was an increase in urea and creatinine levels in rats DIAB+SN when compared to controls, C+SN (p<0.001). Rats from the DIAB+CR group had a significant reduction in urea and creatinine, compared to the DIAB+NS group (p<0.001). There were no significant differences in urea and creatinine comparing the C+NS and DIAB+CR groups. The rats from the DIAB+NS group had significantly lower levels of CAT, GSH-px and SOD when compared to the normal control rats (p<0.001). In animals from the DIAB+SN group, the levels of these antioxidant enzymes were significantly reduced (p<0.001). The treatment of diabetics with crajiru extract caused a significant increase (p<0.001) in the levels of CAT, GSH-px and SOD, when compared to rats in the BIAB+SN group. Conclusion: The data of the present study confirms that the crajiru extract positively influenced the control of hyperglycemia in diabetic rats. More research is needed to provide a better understanding of the mechanisms of diabetes treatment using crajiru extract and its flavonoids.